The Relationship Of Political Socialization Messages Relations In Social Media Twitter With The Image Of PKS. (Study: Political Socialization PKS Through @PKSejahtera Account) - Munadhil Abdul Muqsith (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2019)
The development of new media provides convenience in communicating and conveying the message, thus leading directly into a meeting without limited space, time and distance, users can easily participate in social interaction. Political parties take advantage of the development of new media in order to disseminate and political information to the public in order to obtain a good image. The Justice and Prosperous Party or sometime called PKS utilizing twitter as a social media in order to convey the message of political socialization through the official account DPP @PKSejahtera to 159.500 followers. This research is about the relationship of political socialization messages relations in social media twitter with the image of PKS. (Study: Political Socialization PKS through @PKSejahtera account). Purpose of this study is 1) how much the relationship of political socialization messages in social media Twitter with the image of PKS. This research method uses a quantitative approach. These results indicate that there is a relationship between socialization message via twitter to the image. The highest relationship found in the relationship of political socialization message with variable perception in the indicator 's political image.Keywords : Political Socialization Messages, Prosperous Justice Party, Twitter, Image.